"Development Without Policy": Tourism Planning and Research Needs in Cameroon, Central Africa. Issue 6 (2nd November 2019) - Harilal, Vyasha; Tichaawa, Tembi Maloney; Saarinen, Jarkko
ABSTRACT: Tourism is increasingly seen as a pathway to development. However, a condition for the developmental role of tourism is that it is properly planned and managed. This is usually based on specific tourism policy frameworks and research providing guidance and targets for planning and development actions. This research note is contextualised within a tourism planning and development situation in which tourism policy guidelines are missing, and supporting tourism research is extremely limited, with the case focusing on the emerging economy and tourism destination of Cameroon, in Central Africa. The paper provides a thematic overview of tourism research in the country, outlining the key issues and challenges in the national tourism governance and policy landscape. It is concluded that, to capitalise on the benefits of the growing industry, there is an urgent need for national tourism policies, supported by more intensive research on tourism and its role in development.